2020
DOI: 10.1007/s13311-020-00865-y
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Astrocyte Transduction as Gene Therapy for Megalencephalic Leukoencephalopathy

Abstract: Megalencephalic leukoencephalopathy with subcortical cysts (MLC) is a rare genetic disorder belonging to the group of vacuolating leukodystrophies. It is characterized by megalencephaly, loss of motor functions, epilepsy, and mild mental decline. In brain biopsies of MLC patients, vacuoles were observed in myelin and in astrocytes surrounding blood vessels. There is no therapy for MLC patients, only supportive treatment. We show here a preclinical gene therapy approach for MLC using the Mlc1 knock-out mouse. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 47 publications
(70 reference statements)
0
10
0
Order By: Relevance
“…A dose-escalation study demonstrated a correlation between MLC1 expression and the degree of correction of the white matter vacuolation in the cerebellum of treated KO mice (Sánchez et al, 2020). However, wild-type animals injected with MLC1 did not show any deleterious effect, contrary to what was reported in the MLC1 over-expressing transgenic animal (Sugio et al, 2017), reinforcing the safety of the strategy and indicating that only supra-physiological levels of MLC1 may be toxic.…”
Section: Gene Therapy For Mlcmentioning
confidence: 72%
See 2 more Smart Citations
“…A dose-escalation study demonstrated a correlation between MLC1 expression and the degree of correction of the white matter vacuolation in the cerebellum of treated KO mice (Sánchez et al, 2020). However, wild-type animals injected with MLC1 did not show any deleterious effect, contrary to what was reported in the MLC1 over-expressing transgenic animal (Sugio et al, 2017), reinforcing the safety of the strategy and indicating that only supra-physiological levels of MLC1 may be toxic.…”
Section: Gene Therapy For Mlcmentioning
confidence: 72%
“…Moreover, particularly for lumbar puncture, it can be performed in an outpatient setting, as is much less invasive than intracranial administration. In the MLC mouse model, the best results were obtained by delivering the vector into the CSF by occipital subarachnoid administration, achieving a high percentage of transduction of the cerebellum without damaging the brain parenchyma, allowing for a more localized and efficient action and avoiding non-specific effects due to systemic expression (Sánchez et al, 2020). By this route, we efficiently achieved transduction in most of the cerebellar parenchyma, with the highest efficacy in the Bergmann glia, where MLC1 is highly expressed (Figure 4).…”
Section: Gene Therapy For Mlcmentioning
confidence: 99%
See 1 more Smart Citation
“…MLC1 is exclusively expressed in gray and white matter astrocytes including cerebellar Bergmann glia in the CNS. In a recently published murine MLC1 knockout model that mirrors the spongiform phenotype of the human disease, a single astrocyte targeted AAV.rh10- GFAP-MLC1 gene replacement prevented vacuolization when administered before disease onset at 5 months, and even at 15 months provided near complete remission of vacuolization ( Sánchez et al, 2020 ). While likely due to the advanced age at infusion, the authors observed relatively poor transduction in the CNS following IT or ICV delivery.…”
Section: Leukodystrophies That Require Astrocyte Targetingmentioning
confidence: 99%
“…These genetically rare myelin diseases are often characterized in early childhood with several clinical presenting forms, namely hypotonia, ataxia, and seizures (Traeger and Rapin, 1998;Barkovich, 2005; van der Knaap and Bugiani, 2017). Some symptoms have also been observed of advancing into more severe stages such as hydrocephaly and megalencephaly (Matalon et al, 1988;Bugiani et al, 2010;Desai and Grimm, 2013;Sánchez et al, 2020). Consequently, many diagnosed patients can progressively develop significant debilitation and cognitive impairment, thus negatively affecting their quality of life and contributing to emotional and financial burdens on their families.…”
Section: Introductionmentioning
confidence: 99%